2022
DOI: 10.1038/s41598-022-09410-7
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 spike protein induces cognitive deficit and anxiety-like behavior in mouse via non-cell autonomous hippocampal neuronal death

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is accompanied by chronic neurological sequelae such as cognitive decline and mood disorder, but the underlying mechanisms have not yet been elucidated. We explored the possibility that the brain-infiltrating SARS-CoV-2 spike protein contributes to the development of neurological symptoms observed in COVID-19 patients in this study. Our behavioral study showed that administration of SARS-CoV-2 spike protein S1 subunit (S1 protein) to mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 41 publications
3
31
0
Order By: Relevance
“…Additionally, tissue regions with microglial nodules, had increased axonal damage as measured by amyloid precursor protein deposits, which is a biomarker used to identify persistent damage after traumatic brain injury [ 36 , 64 ]. Microglial activation induced by injection of S1 into the meninges of rats correlated with sickness behavior, anxiety, and cognitive deficits [ 59 , 65 ]. A mouse model of mild COVID-19 found that activated microglia persisted for up to 7 weeks post infection, suggesting that microglia could be partly responsible for neurological PASC [ 22 ].…”
Section: Cns Resident Immunity and Sars-cov-2mentioning
confidence: 99%
“…Additionally, tissue regions with microglial nodules, had increased axonal damage as measured by amyloid precursor protein deposits, which is a biomarker used to identify persistent damage after traumatic brain injury [ 36 , 64 ]. Microglial activation induced by injection of S1 into the meninges of rats correlated with sickness behavior, anxiety, and cognitive deficits [ 59 , 65 ]. A mouse model of mild COVID-19 found that activated microglia persisted for up to 7 weeks post infection, suggesting that microglia could be partly responsible for neurological PASC [ 22 ].…”
Section: Cns Resident Immunity and Sars-cov-2mentioning
confidence: 99%
“…Several studies have examined BBB function in animal models of SARS-CoV-2 infection and in postmortem tissue to understand the impact of acute infection on BBB integrity. The spike protein of SARS-CoV-2 was shown to cross the BBB while direct intrahippocampal injection induced cognitive de cits and anxiety-like behaviour in mice 32,55 . In samples from patients who died during the initial wave of COVID in 2020, Lee et al showed brinogen extravasation and evidence of overactivation of the coagulation system 19,20 while Wenzel et al found string vessels, pathological blood vessels without endothelial cells 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Lung tissue homogenates from mice on alcohol diet showed the overexpression of ACE2 [ 21 ]. The S1 subunit of the SARS-CoV-2 spike protein exerted hippocampal neuronal cell death in mice, affecting brain functions [ 65 ]. More additional studies are needed to evaluate the safety of S-protein subunits on all organs and systems.…”
Section: Protein Subunit Vaccines and Alcoholmentioning
confidence: 99%